Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1111/j.1467-9914.2010.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Labour Market Income: Evidence from Longitudinal Data

Abstract: This study contributes to the literature on how personality is rewarded in the labour market by examining the relationship between personality and labour market income. Our results suggest that adulthood extraversion is positively associated with income when education, work experience, and unemployment history, measured prospectively from longitudinal data, are controlled for. In addition, childhood constructiveness indicating active and well-controlled behaviour has a positive association with income in adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 50 publications
(77 reference statements)
4
36
0
Order By: Relevance
“…Extraversion refers to the individual's need for attention and social interaction, warmth, and gregariousness. As shown by Viinikainen et al (2010) and Nandi and Nicoletti (2009) it is positively associated with earnings. Openness to…”
Section: Measures Of Noncognitive Skillsmentioning
confidence: 87%
“…Extraversion refers to the individual's need for attention and social interaction, warmth, and gregariousness. As shown by Viinikainen et al (2010) and Nandi and Nicoletti (2009) it is positively associated with earnings. Openness to…”
Section: Measures Of Noncognitive Skillsmentioning
confidence: 87%
“…Michel et al in his metaanalytic review have shown extroversion is related to negative work-nonwork spillover (β = -0.08), and is related to positive worknonwork spillover (β = 0.27) (28). Viinikainen et al by a longitudinal research on personality and unemployment, found that extroversion had negative associations with cumulative unemployment and the number of unemployment spells (9).…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicated that neuroticism was significantly related to length of prior employment for people who had a high school education or less but not for people who had postsecondary education (31). Viinikainen et al by a longitudinal research on personality and unemployment, found that neuroticism was associated with longer durations of individual unemployment spells (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Connections have been documented between personality characteristics and years of schooling (for a review, see Almlund et al, 2011), the probability of obtaining a degree (Almlund et al, 2011;Carneiro et al, 2007;Coleman and DeLeire, 2003) and the probability of dropping out (Báron and Cobb-Clark, 2010;Coneus et al, 2008;Segal, 2006). In terms of labor market outcomes, significant linkages have been found between personality characteristics and earnings, occupational choices, labor force participation and employment (for example, Borghans et al, 2008;Bowles et al, 2001a,b;Braakmann, 2009;Heckman et al, 2006;Heineck, 2011;Linz and Semykina, 2009;Mueller and Plug, 2006;Nyhus and Pons, 2005;Osborne Groves, 2005;Semykina and Linz, 2007;Uysal and Pohlmeier, 2011;Viinikainen et al, 2010;Viinikainen and Kokko, 2012).…”
Section: Introductionmentioning
confidence: 99%